Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Indole metabolites produced by Lactobacillus acidophilus impedes bisphenol F- aryl hydrocarbon receptor interaction and ameliorates bisphenol F induced depression-like changes - Miaoyang Hu; Ayiguzaili Manglike; Xiaozhu Li; Jin Wei; Xinyu Lou; Jing Liu; Zhiru Tang; Weiping He; Guixiang Ji; Wenjuan Wang; Tengfei Ma; Rong Gao; et al. (Journal of Hazardous Materials, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Distribution and transport of trace organic contaminants from land to the coastal sea - Shi-Jie Lv; Ting Pan; Rui Tang; Jun-Rong Liang; Hui He; Lei Mai (Marine Pollution Bulletin, 2026)

Enrichment of organophosphate esters in the surface microlayer of a subtropical urban lake: Phase partitioning dynamics and air-water exchange implications - Mingfu Lin; Tao He; Rong Wang; Lixiang Zhong; Menghuan Zhang; Jun Wang; Yumei Huang (Journal of Hazardous Materials, 2026)

Integrative bulk and single-cell transcriptomic analyses reveal nucleus pulposus cell fibrosis as a therapeutic target in intervertebral disc degeneration and identify quercetin as a potential antifibrotic agent - Peilin He; Jun Tao; Guo Li; Ye Mu; Rong Hu; Junming Chen; Wenqi Feng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Widespread incongruence in the phylogenomics of the ancient land plant lineage, Selaginellaceae (lycophytes) - Jing Zhao; Hong Yu; Carl J. Rothfels; Jian-Jun Yang; Shao-Li Fang; Zhao-Rong He; Li-Bing Zhang; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2026)

Cerium isotopic compositions of deep-sea sediments: implications for geochemical behavior of rare earth elements in the pelagic seafloor - Ganglan Zhang; Jianghao Bai; Mingyu Zhao; Pengcong Wang; Yangtao Zhu; Jun Cao; Hao Wu; Rong Xu; Gaowen He; Gangjian Wei; Yinan Deng (Geochimica et Cosmochimica Acta, 2026)

Investigation of the Shallow Structure of the Hami Basin Northern Margin Fault Using Comprehensive Geophysical Methods - Guang-hong Ju; Xiao-dong He; Rong-ying Zheng; Yan-ling Liu; Jun-qi Duan; Jun Shen; Zhi-tao Gao (Applied Geophysics, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

The application of nutrients in enhancing drought tolerance of secretohalophyte Atriplex canescens in the desert regions of Northwest China - Jian-jun Kang; Wen-zhi Zhao; Zhi-bin He; Bing Liu; Rong Yang; Hai Zhou; Dong-Mei Zhang (Plant and Soil, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

A soil–water retention model with differentiated adsorptive and capillary regimes - Zhang-Rong Liu; Wei-Min Ye; Yu-Jun Cui; He-Hua Zhu; Yong-Gui Chen; Qiong Wang (Computers and Geotechnics, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

SIRT5: a potential target for discovering bioactive natural products - Yuwei Xie; Nali Cai; Xiaohua Liu; Liangliang He; Yiming Ma; Changyu Yan; Juan Liang; Shu-Hua Ouyang; Ao Luo; Yingzhi He; Jun Lu; Dang Ao; et al. (Journal of Natural Medicines, 2025)
Silent information regulator 5 (SIRT5) is the fifth member of the sirtuin family, which is mainly expressed in mitochondrial matrix. SIRT5 plays a key role in metabolism and antioxidant responses, and is an important regulator for maintaining intracellular homeostasis. Given its involvement in multiple cellular processes, dysregulation of SIRT5 activity is associated with a variety of diseases. This review explores the structural characteristics of SIRT5 that influence its substrate specificity, highlights recent research advances, and summarizes its four key enzymatic activities along with their corresponding substrates in disease contexts. We also discuss the natural products that modulate SIRT5 activity and identify potential targets of SIRT5 through virtual docking, which may provide new therapeutic avenues. Although the mechanism of SIRT5 in diseases needs to be further elucidated and deglutathionylation activities are still at an early stage, targeting SIRT5 and its substrates holds significant promise for the development of novel therapeutics. Graphical abstract

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

The effect of Desulfovibrio caledoniensis and Pseudomonas aeruginosa on the corrosion behaviour of 70Cu-30Ni alloy - Li-Jun He; Zheng-Hui Qiu; Shao-Xia Ma; Rong-Chang Zeng; Cun-Guo Lin (Biofouling, 2024)

Genomic analysis of hypoxia-tolerant population of the Chinese mitten crab (Eriocheir sinensis) - Feng-yuan Yan; Yuan-feng Xu; Wen-rong Feng; Qing-hong He; Guo-an Hua; Wen-jing Li; Pao Xu; Jun Zhou; Yong-kai Tang (Fish & Shellfish Immunology, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

The response of Martian photoelectron boundary to the 2018 global dust storm - Yuqi Wang; Jun Cui; Yong Wei; Zhaopeng Wu; Kai Fan; Zhaojin Rong; Fei He; Yutian Cao; Jiawei Gao (Science China Earth Sciences, 2024)

Assessment of the hormesis effect and toxic damage of short-term low-dose aflatoxin B1 in grass carp (Ctenopharyngodon idellus) - Jin-long Li; Jia-rong Guo; Pei Wang; Jun-zhi Zhang; Zhi-gang He; Jin-long Wang; Yi Hu (Frontiers in Marine Science, 2024)
The present study was conducted to evaluate the hormesis and toxicity of short-term low-dose aflatoxin B1 in grass carp ( Ctenopharyngodon idellus ). Triplicate isonitrogenous and isocaloric aflatoxin B1 diets—CD (control, 0 ug/kg), D1 (20 ug/kg), and D2 (500 ug/kg)—were prepared and fed to grass carp with an initial mean body weight of (15.2 ± 0.1) g for 56 days. The results showed that the weight gain rate and specific growth rate of grass carp fed diet D2 were significantly higher, and the feed coefficient and crude fat content of the whole body were significantly lower ( P < 0.05) compared with those fed diet CD. Serum superoxide dismutase content of grass carp fed D1 diet increased significantly ( P < 0.05) with an increasing dose of aflatoxin B1, but when the dose reached 500 ug/kg (D2), serum superoxide dismutase, complement C3, and immunoglobulin M of grass carp decreased significantly ( P < 0.05), while malondialdehyde increased significantly ( P < 0.05). After short-term feeding of aflatoxin B1-containing diets (D1 and D2), liver body index, visceral body index, serum total cholesterol, triglyceride, and urea nitrogen content of grass carp increased significantly ( P < 0.05), total bile acid secretion decreased significantly ( P < 0.05), and structural damages such as increase in vacuoles, organizational structure loosening, and nucleus translocation were observed in the liver. Meanwhile, liver function indexes such as serum alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase increased significantly with the increase of aflatoxin B1 dose ( P < 0.05). In addition, the height of intestinal villi, crypt depth, villus–crypt ratio, and tubular cell number, as well as the content of trypsin and lipase activities in the intestine of grass carp in the D2 group, were significantly higher than those in the CD group ( P < 0.05). In conclusion, after a short-term intake of low doses of aflatoxin B1 (≤500 ug/kg), the toxicological damage of aflatoxin B1 was pronounced, although it produced a certain degree of hormesis on the growth performance and intestinal structure and function of grass carp. At a dose of 20 ug/kg, the non-specific immune system and liver structure and function of grass carp showed obvious toxic damage.

Sustainable design of photo-Fenton-like oxidation process in actual livestock wastewater through the highly dispersed FeCl3 anchoring on a g-C3N4 substrate - Yanfang Feng; Yunyi Liang; Chenman Ding; Yue Jiang; Hongmei Jin; Shaopeng Rong; Jun Wu; Shiying He; Changlei Xia; Lihong Xue (Water Research, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Organic substitution regime with optimized irrigation improves potato water and nitrogen use efficiency by regulating soil chemical properties rather than microflora structure - Xiya Wang; Binggeng Yang; Lingling Jiang; Shicheng Zhao; Mengjiao Liu; Xinpeng Xu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Field Crops Research, 2024)

Enhanced anaerobic digestion performance and sludge filterability by membrane microaeration for anaerobic membrane bioreactor application - Chun-Hai Wei; Zheng-Wei Wang; Jian-Hua Dai; Kang Xiao; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Huu Hao Ngo (Bioresource Technology, 2024)

Fate of sulfamethoxazole in wetland sediment under controlled redox conditions - Yujie He; Longxue Jiang; Xuan Wu; Wenhui Zhang; Yao Zong; Jiacheng Wang; Jinmei Chen; Jun Shan; Deyang Kong; Rong Ji (Water Research, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Response of soil microbial properties in the life cycle of potatoes to organic substitution regimes in North China - Xiya Wang; Shicheng Zhao; Xinpeng Xu; Mengjiao Liu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Soil and Tillage Research, 2024)

Underlying the inhibition mechanisms of sulfate and lincomycin on long-term anaerobic digestion: Microbial response and antibiotic resistance genes distribution - Li Xie; Jiaxin Zhu; Jing Xie; Jun Xu; Rong He; Wenbiao Wang (Science of The Total Environment, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

Corrigendum to “Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation” [Chemosphere 301 (2022) 134722] - Wan-Peng Zhang; Kun Wu; Junyi Zhao; Jun He; Leiping Wang; Hang Xiao; Jian-Bing Guo; Jian-Rong Li (Chemosphere, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Pipeline positioning by the surface-to-borehole electromagnetic induction method in a clayey deposit - Guo-Wei Li; Zhi-Ming Ye; Yang Zhou; Guan-Jun He; Guang-Yu Liu; Xin-Rong He (Applied Geophysics, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Cuproptosis: copper-induced regulated cell death - Wen-Jun Duan; Rong-Rong He (Science China Life Sciences, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Cassiterite oxygen isotopes in magmatic-hydrothermal systems: in situ microanalysis, fractionation factor, and applications - Yang Li; Sheng He; Rong-Qing Zhang; Xian-Wu Bi; Lian-Jun Feng; Guo-Qiang Tang; Wen-Zhong Wang; Fang Huang; Xian-Hua Li (Mineralium Deposita, 2022)

The adsorption mechanism of CF4 on the surface of activated carbon made from peat and modified by Cu - Rong Pan; Wei Dong; Yanni Guo; Yining Tang; Jun Shang; Lei Zhou; Deliang He (Environmental Science and Pollution Research, 2022)

Phenomic and metabolomic responses of roots to cadmium reveal contrasting resistance strategies in two rice cultivars (Oryza sativa L.) - Chong Liu; Mo-ming Lan; Er-kai He; Ai-jun Yao; Guo-bao Wang; Ye-tao Tang; Rong-liang Qiu (Soil Ecology Letters, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Discovery of new small-molecule cyclin-dependent kinase 6 inhibitors through computational approaches - Xiaojiao Luo; Yu Zhao; Pan Tang; Xingkai Du; Feng Li; Qingying Wang; Rong Li; Jun He (Molecular Diversity, 2021)

Geochemical characteristics and geological significance of chert nodules in Qixia formation, Pingding Mountain, lower Yangtze Plate - Jun Li; Lu-wang Chen; Chun-ming Hao; Jie Zhang; Song Chen; He-rong Gui (Journal of Mountain Science, 2021)

Numerical investigation of heat transfer effect on flow behavior in a single fracture - Jie Tan; Guan Rong; Renhui He; Jie Yang; Jun Peng (Arabian Journal of Geosciences, 2020)

Transcriptome analysis reveals genes associated with leaf color mutants in Cymbidium longibracteatum - Jiang Yu; Wang Qiang; Shen Qin-Qin; Zhuo Bi-Ping; He Jun-Rong (Tree Genetics & Genomes, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

Two highly oxygenated Ergosterols from cultures of the Basidiomycete Conocybe siliginea - Chao-Jun Pu; Yue-Ling Peng; Zheng-Hui Li; Juan He; Rong Huang; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Identifying the Pollution Characteristics of Atmospheric Polycyclic Aromatic Hydrocarbons Associated with Functional Districts in Ningbo, China - Lei Tong; Cheng-Hui Peng; Zhong-Wen Huang; Jing-Jing Zhang; Xiao-Rong Dai; Hang Xiao; Neng-Bin Xu; Jun He (Bulletin of Environmental Contamination and Toxicology, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Diversity of herbaceous plants and bacterial communities regulates soil resistome across forest biomes - Hang‐Wei Hu; Jun‐Tao Wang; Brajesh K. Singh; Yu‐Rong Liu; Yong‐Liang Chen; Yu‐Jing Zhang; Ji‐Zheng He (Environmental Microbiology, 2018)
Summary Antibiotic resistance is ancient and prevalent in natural ecosystems and evolved long before the utilization of synthetic antibiotics started, but factors influencing the large‐scale distribution patterns of natural antibiotic resistance genes (ARGs) remain largely unknown. Here, a large‐scale investigation over 4000 km was performed to profile soil ARGs, plant communities and bacterial communities from 300 quadrats across five forest biomes with minimal human impact. We detected diverse and abundant ARGs in forests, including over 160 genes conferring resistance to eight major categories of antibiotics. The diversity of ARGs was strongly and positively correlated with the diversity of bacteria, herbaceous plants and mobile genetic elements (MGEs). The ARG composition was strongly correlated with the taxonomic structure of bacteria and herbs. Consistent with this strong correlation, structural equation modelling demonstrated that the positive effects of bacterial and herb communities on ARG patterns were maintained even when simultaneously accounting for multiple drivers (climate, spatial predictors and edaphic factors). These findings suggest a paradigm that the interactions between aboveground and belowground communities shape the large‐scale distribution of soil resistomes, providing new knowledge for tackling the emerging environmental antibiotic resistance.

Mixed Cadzow filtering method in fractional Fourier domain - Zhong-Lin Cao; Jun-Xing Cao; Fu-Rong Wu; Guang-Ming He; Qiang Zhou; Yu-Lin Wu (Applied Geophysics, 2018)

Cyclooxygenase-2 (COX-2) polymorphism rs689466 may contribute to the increased susceptibility to post-traumatic osteomyelitis in Chinese population - Lei Wang; Nan Jiang; Qing-rong Lin; Cheng-he Qin; Yan-jun Hu; Bin Yu (Infectious Diseases, 2017)

Two new Anti-TMV active chalconoid analogues from the root of Phyllanthus emblica - He Yan; Li Rong Han; Xing Zhang; Jun Tao Feng (Natural Product Research, 2017)

Synthesis and evaluation of multifunctional ferulic and caffeic acid dimers for Alzheimer’s disease - Xi-xin He; Xiao-hong Yang; Rui-ying Ou; Ying Ouyang; Sheng-nan Wang; Zi-wei Chen; Shi-jun Wen; Rong-biao Pi (Natural Product Research, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Characteristics of gravity anomalies and prediction of volcanosedimentary boron deposit distribution in the Xiongba area, Tibet - Li-Rong Song; Chang-Qing Yu; Gui-Hua Li; Yang-Yang Feng; Jun-Jie He (Applied Geophysics, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Genetic diversity revealed by morphological traits and ISSR markers in 48 Okras (Abelmoschus escullentus L.) - Cong-Ying Yuan; Ping Wang; Pang-Pang Chen; Wen-Jun Xiao; Cheng Zhang; Shuai Hu; Ping Zhou; Hong-Ping Chang; Zhuang He; Rong Hu; Xiu-Tao Lu; Jia-Zhuo Ye; et al. (Physiology and Molecular Biology of Plants, 2015)

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Isolation and characterization of 18 microsatellites for Aconitum vilmorinianum Kom. (Ranunculaceae) using next-generation sequencing technology - Jun He; Zhi-Rong Zhang; Jun-Bo Yang; Hong Wang; Jing Meng (Conservation Genetics Resources, 2015)

Biological Roles of Olfactory Ensheathing Cells in Facilitating Neural Regeneration: A Systematic Review - Hao Yang; Bao-Rong He; Ding-Jun Hao (Molecular Neurobiology, 2015)

Removal of antibiotics and antibiotic resistance genes in rural wastewater by an integrated constructed wetland - Jun Chen; You-Sheng Liu; Hao-Chang Su; Guang-Guo Ying; Feng Liu; Shuang-Shuang Liu; Liang-Ying He; Zhi-Feng Chen; Yong-Qiang Yang; Fan-Rong Chen (Environmental Science and Pollution Research, 2015)

Fibroblast Growth Factor 4 Is Required but not Sufficient for the Astrocyte Dedifferentiation - Guo-Dong Feng; Bao-Rong He; Fan Lu; Lin-Hong Liu; Lingling Zhang; Bo Chen; Zu-Ping He; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Three dimensional reconstruction of bone-cartilage transitional structures based on semi-automatic registration and automatic segmentation of serial sections - Hua Guo; Zheng-Wei Xu; Bao-Rong He; Ding-Jun Hao; Wei-Guo Bian (Tissue Engineering and Regenerative Medicine, 2014)

Phagocytic Removal of Neuronal Debris by Olfactory Ensheathing Cells Enhances Neuronal Survival and Neurite Outgrowth via p38MAPK Activity - Bao-Rong He; Song-Tao Xie; Ming-Mei Wu; Ding-Jun Hao; Hao Yang (Molecular Neurobiology, 2014)

Interval Q inversion based on zero-offset VSP data and applications - Gu-Lan Zhang; Xi-Ming Wang; Zhen-Hua He; Jun-Xing Cao; Ke-En Li; Jiao-Jun Rong (Applied Geophysics, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Environmental Investigations and Molecular Typing of Aspergillus in a Chinese Hospital - Jun-hong Ao; Zhen-feng Hao; He Zhu; liang Wen; Rong-ya Yang (Mycopathologia, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Erratum to: Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Olfactory responses of Neoseiulus cucumeris (Acari: Phytoseiidae) to odors of host plants and Frankliniella occidentalis (Thysanoptera: Thripidae)–plant complexes - Feng Zhong; Yu-Rong He; Yan Gao; Guo-Jun Qi; Chen-Yin Zhao; Li-Hua Lu (Arthropod-Plant Interactions, 2011)

Knockdown of ribonuclease inhibitor expression with siRNA in non-invasive bladder cancer cell line BIU-87 promotes growth and metastasis potentials - Junxia Chen; Xi Ou-Yang; Juan Gao; Jun Zhu; Xiaoyan He; Jiang Rong (Molecular and Cellular Biochemistry, 2011)

Antigenically dominant proteins within the human liver mitochondrial proteome identified by monoclonal antibodies - YanFang Ju; JinJu Yang; Rong Liu; XiaoLan Liu; XueMei Du; Li Liu; ZhiCheng Chen; Jun Chi; ShuEr Liu; Yuan Gao; JianEn Gao; ShunChang Jiao; et al. (Science China Life Sciences, 2011)

A mini review of MAR-binding proteins - Tian-Yun Wang; Zhong-Min Han; Yu-Rong Chai; Jun-He Zhang (Molecular Biology Reports, 2010)

Curcumin prevents liver fibrosis by inducing apoptosis and suppressing activation of hepatic stellate cells - Jian-Chang Shu; Ya-Jun He; Xia Lv; Guo-Rong Ye; Le-Xin Wang (Journal of Natural Medicines, 2009)

Epigallocatechin-3-gallate affects the growth of LNCaP cells via membrane fluidity and distribution of cellular zinc - Jun-guo Yang; Hai-ning Yu; Shi-li Sun; Lan-cui Zhang; Guo-qing He; Undurti N. Das; Hui Ruan; Sheng-rong Shen (Journal of Zhejiang University-SCIENCE B, 2009)

A preliminary study on the teratogenesis of dexamethasone and the preventive effect of vitamin B12 on murine embryonic palatal shelf fusion in vitro - Sheng-jun Lu; Wei He; Bing Shi; Tian Meng; Xiao-yu Li; Yu-rong Liu (Journal of Zhejiang University-SCIENCE B, 2008)

Heregulin protects mesenchymal stem cells from serum deprivation and hypoxia-induced apoptosis - Chun Gui; Jian An Wang; Ai Na He; Tie Long Chen; Rong Hua Luo; Jun Jiang; Xin Yang Hu; Xiao Jie Xie (Molecular and Cellular Biochemistry, 2007)

Thermal effects of building’s external surfaces in city - Yi-ping Zhang; Yun-ling He; Yu-hong Liu; You-xin Ma; You-rong Li; Jun-xia Dou (Chinese Geographical Science, 2004)